The political thought of Peter B. Struve, 1870-1917 (Urbana Illinois, 1957)
With bibliogr. Thesis Urbana, University of Illinois. Facsimile reprint: Ann Arbor, Michigan, University Microfilms, 1962. ("O-P Book").